PENGAWASAN PEMERINTAH TERHADAP PENGGUNAAN JALAN NAPAL DI KECAMATAN PERANAP INDRAGIRI HULU 2024 - Afriyandi , (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
This study examines government supervision over the use of Napal Road by coal transportation vehicles in Peranap District, Indragiri Hulu Regency. A qualitative descriptive approach was employed through observation, interviews, and documentation. The findings indicate that supervision has been conducted through inter-agency coordination, road monitoring, and control efforts over heavy vehicles. Nevertheless, the effectiveness of supervision remains limited due to resource constraints, the high intensity of coal transportation activities, weak compliance with load regulations, and insufficient coordination among stakeholders. The study concludes that stronger supervision, better coordination, and greater corporate participation are required to maintain road infrastructure sustainability. Keywords: Government Supervision, Road Infrastructure, Coal Transportation, Public Policy.